Salicylic Acid Spraying Affects Secondary Metabolites and Radical Scavenging Capacity of Drought-Stressed Eriocephalus africanus L. - Noha Khalil; Sameh S. Elhady; Reem M. Diri; Mostafa I. Fekry; Mokhtar Bishr; Osama Salama; Soheir M. El-Zalabani (Agronomy, 2022)
Drought is among the most common abiotic stresses that significantly influence plants’ growth and metabolic activities. In this study, Eriocephalus africanus L. (Asteraceae) was exposed to three levels of drought stress (irrigation with 75, 50, and 25% field capacity), together with foliar spraying of a plant hormone, salicylic acid (1, 2, and 3 mM SA), to observe the effect of drought stress and SA on its secondary metabolites. These growing conditions efficiently affected its total flavonoid and polyphenol contents (TFC and TPC, respectively). TFC and TPC increased by 53% and 35%, respectively, in stressed plants. Consequently, the radical scavenging activity improved by 140%. UPLC-ESI-MS/MS profiles of the extracts of control and stressed plants were assessed. Among identified polyphenols, 3,4-dicaffeoylquinic acid predominated in both samples, although it was detected in a greater percentage of stressed plants. Essential oils hydro-distilled from the plants showed a higher yield (1.05 ± 0.03% v/w) in stressed plants. Artemisia ketone prevailed in all oil samples’ GC/MS chromatograms, with a higher yield (42%) recorded in stressed plants. In conclusion, drought stress and SA spraying triggered the production of phenolic and essential oil components and increased the radical scavenging activity of E. africanus. Thus, agricultural conditions are optimized to provide a continuous supply of plant materials with appropriate amounts of bioactive constituents for economic industrialization.